SCREENING OF COLD ETHYL ALCOHOL EXTRACT OF CARICA PAPAYA FOR INSECTICIDAL PROPERTIES AGAINST THE LEPIDOPTERAN PEST SPODOPTERA LITURA FABRICIUS - DESHIMUKHE, PRATIBHA V.; HOOLI, ASHOKA.; HOLIHOSUR, S.N. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2011)
The tobacco caterpillar Spodoptera litura Fabricius has emerged as a serious and dominant pest on many agricultural crops causing enormous losses. The use of plant extracts of various medicinal plants against the different developmental stages of S. litura to test their efficacy in organic farming is the need of the day. A cold ethyl alcohol extract of leaves of Carica papaya at different concentrations from 0.5 to 25 per cent was administered to lab-reared; pre starved fourth instar larvae topically as well as through food. The fourth instar larvae treated topically with the 25 per cent extract exhibited a total larval mortality of 68.33+ 1.66 per cent and the maximum total per cent mortality was 76.66+ 1.66 during its development to the adult stage. The larvae that were administered the plant extract through their food showed a per cent total mortality of 83.33 + 1.66 at 25 per cent concentration, of which 71.66 + 1.66 per cent was at the larval stage itself. Deformities and mortality were observed in the dead larvae and pupae for both the tests. However, deformities in adults appeared for topical treatment alone. The LCso and coo for topical application was 17.34 and 36.65 respectively.The same for leaf application was 22.68 and 61.03. The botanical also exhibited phagodeterrent properties.